2015
DOI: 10.1002/mc.22340
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NANOG in cancer cells

Abstract: As one of the key pluripotency transcription factors, NANOG plays a critical role in maintaining the self-renewal and pluripotency in normal embryonic stem cells. Recent data indicate that NANOG is expressed in a variety of cancers and its expression correlates with poor survival in cancer patients. Of interest, many studies suggest that NANOG enhances the defined characteristics of cancer stem cells and may thus function as an oncogene to promote carcinogenesis. Therefore, NANOG expression determines the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 82 publications
3
53
1
3
Order By: Relevance
“…Interestingly, our results on the self-renewal ability of cells through clonal analysis, demonstrated that the capability to form MS is directly correlated to CD133 expression (D283>D341>DAOY), as already reported by other authors [30,46]. This turns out in a significantly higher level of main transcription factors as BMI1, NANOG, and OCT4, all involved in the gene regulatory networks controlling stem cell properties [47][48][49][50]. In agreement with these data, when engrafted in vivo, D283 cells give rise to tumors with high efficiency.…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, our results on the self-renewal ability of cells through clonal analysis, demonstrated that the capability to form MS is directly correlated to CD133 expression (D283>D341>DAOY), as already reported by other authors [30,46]. This turns out in a significantly higher level of main transcription factors as BMI1, NANOG, and OCT4, all involved in the gene regulatory networks controlling stem cell properties [47][48][49][50]. In agreement with these data, when engrafted in vivo, D283 cells give rise to tumors with high efficiency.…”
Section: Discussionsupporting
confidence: 84%
“…In addition to revealing an underlying malignancy, the exosomal protein cargo functions to enhance the progression of metastasis of ovarian tumors ( Table 1). For example, Nanog is a transcription regulator involved in tumor cell proliferation and self-renewal of cancer stem cells [31]. Nanog expression is significantly greater in exosomes sampled from the ascites of high-grade serous ovarian cancer compared to benign peritoneal fluid [32].…”
Section: Ovarian Cancer-exosomesmentioning
confidence: 99%
“…Their role in normal adult tissues remains largely unknown and their activation is currently associated with cancer pathogenesis. Tumors positively genotyped for Oct4, Sox2, or Nanog are associated with a poor prognosis and increased metastasis by enabling cancerous cells to undergo sustained proliferation and evade cell death, suggesting that these genes may confer a stem-like state onto the cancer cells (Gong et al, 2015;Samardzija et al, 2012;Weina and Utikal, 2014).…”
Section: ) Osteogenesis Is Induced By Expression Of Runx2mentioning
confidence: 99%